Participatory Natural Resource Management in Watersheds: Concepts, Issues and Challenges for Research - Johnson, Nancy; Knox, Anna (Annals of Arid Zone, 2016)
This paper describes a "new watershed approach" characterized by an ecosystems perspective; collaborative and multi-stakeholder decision process; and multi-scale action and analysis. The approach evolved in response to the failures of many past top-down watershed programs based on physical planning for water management. It also reflects changes in the nature of watershed management initiatives and new thinking in the broader field of "watershedology" towards more integrated and multidisciplinary analysis of natural resources. Participatory watershed management is closely related to broader changes in the political economy of natural resource management, as reflected in a growing trend towards devolution or decentralization of authority and responsibility. While there is a growing body of case study evidence to support the effectiveness of new participatory approaches, challenges remain to demonstrate impact and to identify generalizable lessons for watershed organizations. Researchers together with other stakeholders, can contribute to better participatory management by developing better methods and tools for stakeholder identification, organization and facilitation; for participatory research and innovation at the landscape scale; and for assessing impact and scaling up.